Glucose metabolism in pigs expressing human genes under an insulin promoter. (10th November 2014) - Wijkstrom, Martin; Bottino, Rita; Iwase, Hayoto; Hara, Hidetaka; Ekser, Burcin; van der Windt, Dirk; Long, Cassandra; Toledo, Frederico G. S.; Phelps, Carol J.; Trucco, Massimo; Cooper, David K. C.; Ayares, David
Abstract Background Xenotransplantation of porcine islets can reverse diabetes in non‐human primates. The remaining hurdles for clinical application include safe and effective T‐cell‐directed immunosuppression, but protection against the innate immune system and coagulation dysfunction may be more difficult to achieve. Islet‐targeted genetic manipulation of islet‐source pigs represents a powerful tool to protect against graft loss. However, whether these genetic alterations would impair islet function is unknown. Methods On a background of α1, 3‐galactosyltransferase gene‐knockout (GTKO)/human (h)CD46, additional genes (hCD39, human tissue factor pathway inhibitor, porcine CTLA4‐Ig) were inserted in different combinations under an insulin promoter to promote expression in islets (confirmed by immunofluorescence). Seven pigs were tested for baseline and glucose/arginine‐challenged levels of glucose, insulin, C‐peptide, and glucagon. Results This preliminary study did not show definite evidence of β‐cell deficiencies, even when three transgenes were expressed under the insulin promoter. Of seven animals, all were normoglycemic at fasting, and five of seven had normal glucose disposal rates after challenge. All animals exhibited insulin, C‐peptide, and glucagon responses to both glucose and arginine challenge; however, significant interindividual variation was observed. Conclusions Multiple islet‐targeted transgenic expression was not associated with an overtly detrimental effect on islet function, suggesting that complex genetic constructs designed for islet protection warrants further testing in islet xenotransplantation models.